Assessment of impact fracture toughness of PP-elastomeric polyolefin blends - Fasce, Laura Alejandra (2002)
The present investigation is concerned with evaluation of the impact fracture toughness of novel blends based on commercial polypropylene homopolymer (PPH) and elastomeric polyolefin (POEs). At room temperature and high load rate, PPH behaves in a brittle manner while the blends exhibited semi-brittle behavior as judged from the nonlinearity in load deflection curves and fracture surface appearance. The challenge of determining reliable toughness values was faced by applying different approaches available in the literature based on fracture mechanics concepts, including corrected linear elastic fracture mechanics (LEFM), equivalent energy concept, and non-LEFM. The fracture toughness data of the blends appeared to be widely scattered in accord with the samples being in the ductile-brittle transition region. In order to provide a consistent description of the entire range of sample behavior, the statistical weakest link model was also applied to the data.